Supersaurio : a novel - El Mehdati, Meryem, (1991-) (Hanover Square Press, 2025)
An uproarious debut novel about a young woman from the Canary Islands whose internship with a supermarket chain reveals the soul-crushing vagaries of modern life. Meryem is twenty-five years old, drinks too much coffee, goes on dates with terrifying men and never says what she really thinks. A Canarian from a Moroccan family, she's just started working as an intern at a mega-chain supermarket, where the only thing she and her boss have in common is their mutual hatred for each other. To pass the time, Meryem begins to write fan fiction starring her office mates. Surrounded by insecure and inept individuals, she reimagines her bland day job through fabricated office crushes and coworker drama. But to get through the daily grind, she's going to have to summon more than just her imagination. Bold, refreshing and darkly comedic, Supersaurio vividly portrays the everyday trials and tribulations of entering your twenties in a world that feels like everything's pitted against you.